Використання інформаційних технологій навчання для формування освітніх траєкторій - Пєвцова, М. О.; Дмитрук, С. С.; Пятайкіна М. І.; Стрілкова, Т. О. (ХНУРЕ, 2025)
The article examines the use of modern information technologies in the development of individual educational trajec-tories for students in technical and physical-mathematical fields. It highlights the growing importance of personalized learning in Ukrainian higher education under wartime conditions, with particular attention to flexibility, adaptability, and digitalization. A comparative analysis of Ukrainian and European approaches shows that both systems aim to en-hance motivation, autonomy, and academic mobility through modular programs, adaptive digital tools, and competen-cy-based learning. The article also presents examples of implementing individual trajectories within the educational and scientific program “Information Microelectronic Systems and Nanotechnology,” demonstrating the integration of information, micro-, and nanotechnologies in contemporary engineering education.
Keywords: формування освітніх траєкторій; інформаційні технології навчання